Synthesis of silver nanoparticles using plant extracts / Nur Fatini Mohamad Nasran and Marlina Mohd Mydin - Mohamad Nasran, Nur Fatini; Mohd Mydin, Marlina (2020)
This review is a comprehensive contribution in a field of green synthesis, characterization and antibacterial activity of silver nanoparticles (AgNPs) using various plant sources. Green synthesis of AgNPs is an environmentally friendly synthesis methods which is becoming more and more popular in field of nanotechnology, with the aim is to avoid hazardous byproduct. Other important advantages of green synthesis of AgNPs lies in its cost effective and in the abundance of raw materials. Use of plants in synthesis of AgNPs among all other green method available is preferred due to their various metabolites which not only act as reducing but as stabilizing or capping agents. Characterization of the synthesized AgNPs performed through TEM, SEM and AFM were comparatively analyzed for their size in term of nanometer and their shape. Besides, the clinically significant of the AgNPs conferring the antibacterial activity by studied against some pathogenic gram-positive and gram-negative bacteria and some pathogenic fungus. This can conclude that due to these unique properties, AgNPs will have a key role in many of the nanotechnology-based processes. This review will help researchers to develop novel AgNPs based drugs using green technology.